Dampak Perubahan Pendapatan Perkapita Terhadap Perubahan Struktur Ekonomi Provinsi Daerah Istimewa Yogyakarta - Sugeng Purwanto; Sugiharti Mulya Handayani (Universitas Sebelas Maret, 2007)
The objective of this research to analyze the effect of change in per capita income to the change in economic structure. The research using time series data for 10 years (1994-2003) with 1993 as the basic year. The data used in this research are The Special Region of Yogyakarta Gross Regional Domestic Product data, The spesial Region of Yogyakarta Export Value data, per capita income, labor data and other relevant data which support the research. Data was collected from Yogyakarta Central Bureau Of Statistic (BPS) and other relevant sources. The data was analyzed using regression analysis. The result of this research showed that primary sector are no longer as the primer sector of Special Region of Yogyakarta and a leap of economics structural changing from primary to tertiary sector.